Basic self‐disturbance, neurocognition and metacognition: A pilot study among help‐seeking adolescents with and without attenuated psychosis syndrome - Koren, Dan; Scheyer, Ravit; Reznik, Noa; Adres, Merav; Apter, Alan; Parnas, Josef; Seidman, Larry J. (Early intervention in psychiatry, 2019)
Aim The goal of this pilot study was to assess the association between basic self‐disturbance (SD) and deficits in neurocognitive and metacognitive functioning among help‐seeking adolescents with and without attenuated psychosis syndrome (APS). Methods Sixty‐one non‐psychotic, help‐seeking adolescents (age 13‐18) were assessed with the examination of anomalous self‐experience, the structured interview for prodromal syndromes and a new metacognitive approach to neurocognitive assessment applied to two non‐social (executive functions and verbal memory) and two social (theory of mind and emotion recognition) domains. After each answer, subjects were also requested to indicate their level of confidence in the answer and to decide whether they desired it to be “counted” toward their total score on the task. Each volunteered answer earned a 5‐cent gain if correct, but an equal fine if wrong. Results As hypothesized, metacognitive monitoring and control had a significant contribution to the prediction of SD over and above neurocognitive functioning and attenuated psychotic symptoms. However, the direction of this association was positive rather than negative. Also, inconsistent with or hypothesis, it was not moderated by the presence of APS. Conclusions These pilot results provide preliminary support a modest association between SD and metacognition, which is not reducible to neurocognition and APS. In addition, they raise an intriguing possibility regarding metacognitive monitoring and control being indicators of hyper‐reflectivity that characterizes individuals with SD. However, further research with larger samples and high‐stress assessment conditions are needed to assess this possibility.